2022
DOI: 10.1111/nph.18287
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c and the transcription factor ABI4 establish a molecular link between mitochondria and ABA‐dependent seed germination

Abstract: During germination, seed reserves are mobilised to sustain the metabolic and energetic demands of plant growth. Mitochondrial respiration is presumably required to drive germination in several species, but only recently its role in this process has begun to be elucidated.Using Arabidopsis thaliana lines with changes in the levels of the respiratory chain component cytochrome c (CYTc), we investigated the role of this protein in germination and its relationship with hormonal pathways.Cytochrome c deficiency cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…Plants with decreased CYTc levels have shorter roots, reduced growth in the presence of sugars, and altered energy metabolism Previous reports showed that cytc double mutant plants with lower CYTc levels (cytc-1b2a and cytc-1b2b) exhibited delayed New Phytologist germination and developmental growth transitions (Racca et al, 2018(Racca et al, , 2022. Since effects on postgerminative growth were mainly attributed to the activity of CYTC-1, one of the two genes encoding CYTc in Arabidopsis thaliana, we analyzed the phenotypic characteristics of cytc-1 single mutant plants (cytc-1a and cytc-1b), previously described in Welchen et al (2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plants with decreased CYTc levels have shorter roots, reduced growth in the presence of sugars, and altered energy metabolism Previous reports showed that cytc double mutant plants with lower CYTc levels (cytc-1b2a and cytc-1b2b) exhibited delayed New Phytologist germination and developmental growth transitions (Racca et al, 2018(Racca et al, , 2022. Since effects on postgerminative growth were mainly attributed to the activity of CYTC-1, one of the two genes encoding CYTc in Arabidopsis thaliana, we analyzed the phenotypic characteristics of cytc-1 single mutant plants (cytc-1a and cytc-1b), previously described in Welchen et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that, while a complete CYTc deficiency is embryo lethal, double mutants in both CYTC genes from Arabidopsis (knock‐down in CYTC‐1 and knock‐out in CYTC‐2 ) show growth defects, including delayed germination and developmental transitions, but are able to complete their life cycle and efficiently reproduce (Welchen et al ., 2012; Racca et al ., 2018, 2022). Here, we found that cytc‐1 single mutant seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations